Expression of Interleukin‐22 in Myasthenia Gravis. (11th July 2013) - Zheng, S.; Dou, C.; Xin, N.; Wang, J.; Wang, J.; Li, P.; Fu, L.; Shen, X.; Cui, G.; Dong, R.; Lu, J.; Zhang, Y.
Abstract IL‐17 and IL‐22 are implicated in the pathogenesis of autoimmune diseases. The roles of IL‐22 in the pathophysiology of myasthenia gravis (MG) remain unsettled. The aim of this study was to investigate the possible relationship between serum IL‐22, IL‐17 levels, anti‐acetylcholine receptor antibody (anti‐AChR Ab) titres and clinical parameters in patients with MG. The serum IL‐22, IL‐17 levels and anti‐AChR Ab titres were tested by enzyme‐linked immunosorbent assay (ELISA), while the expression of IL‐22 and IL‐17 mRNAs in peripheral blood mononuclear cells (PBMC) from healthy and MG subjects were detected by quantitative real‐time PCR (qRT‐PCR). Furthermore, PBMC from 12 patients with generalized MG were purified and treated with recombinant human IL‐22 (rhIL‐22), the IL‐17 levels of supernatant were detected by ELISA. We found that the IL‐17 levels were significantly increased, but IL‐22 levels were significantly decreased in the serum of patients with MG compared with healthy controls. Consistantly, a significant decrease in IL‐22 mRNA levels and an increase in IL‐17 mRNA levels were detected in PBMC collected from patients with MG, compared with healthy controls. A negative correlation between IL‐22 mRNA in PBMC, serum IL‐22 and serum anti‐AChR Ab levels was found in patients with MG. Moreover, in cultured MG PBMC treated with recombinant human IL‐22 (rhIL‐22), the IL‐17 levels were decreased in a dose‐dependent manner. Our findings indicated a possible role of IL‐22 as a protective factor in MG.